2010
DOI: 10.1007/s12583-010-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the creep behavior of garnet at high temperatures and pressures

Abstract: To provide constraints on the rheological properties of garnet, we have experimentally investigated the creep behavior of garnet at high pressures and temperatures using a deformation-DIA. Samples were cold-pressed from a garnet powder and deformed at constant displacement rates ranging from 1.1×10 -5 to 2.6×10 -5 s -1 at high temperatures (1 273-1 473 K) and high pressures (2.4-4.1 GPa). Differential stress and pressure were measured using X-ray diffraction techniques based on the elastic strain of various la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For garnet, we used the flow law from Ji and Martignole () as it appears also the most appropriate for our study. The number of experimental data for garnet is indeed limited and/or most of the time dedicated to higher‐pressure‐temperature values (e.g., Katayama & Karato, ; Li et al, ; Mei et al, ). Moreover, dislocation creep in garnet is never activated in the P‐T conditions of our models.…”
Section: Discussionmentioning
confidence: 99%
“…For garnet, we used the flow law from Ji and Martignole () as it appears also the most appropriate for our study. The number of experimental data for garnet is indeed limited and/or most of the time dedicated to higher‐pressure‐temperature values (e.g., Katayama & Karato, ; Li et al, ; Mei et al, ). Moreover, dislocation creep in garnet is never activated in the P‐T conditions of our models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fluid‐mediated processes, non‐hydrostatic stress at high metamorphic grades can lead to crystal plastic deformation. However, studies have shown that the minerals we consider (garnet, omphacite, and plagioclase) are exceptionally strong, especially when dry (e.g., Bystricky & Mackwell, 2001; Dimanov et al., 1999; Karato et al., 1995; Li et al., 2006; Mei et al., 2010; Rybacki & Dresen, 2004; Wang & Ji, 1999; Zhang & Green, 2007). Consequently, these minerals are likely able to sustain non‐hydrostatic stresses at high metamorphic temperatures (e.g., 500°C–800°C) with limited deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The mafic lower crust initially present in the orogen at the centre of the model and within the mantle transition zone is assumed to follow an eclogite power-law 52 at pressures less than 17.5 GPa . At higher pressures, a garnetite 53 flow law is assumed.…”
Section: Methodsmentioning
confidence: 99%